From Segregation to Inclusion: Children’s Engagement in Urban Public Spaces - Lara-Hernandez, Jose (Taylor and Francis Group, 2025)
This paper explores how urban segregation impacts children’s ability to en-gage with and temporarily appropriate public spaces, a critical aspect of their spatial, social, and cultural development. Using a post-qualitative in-quiry, we integrate Temporary Appropriation and the Speculative Pluriver-sal Imaginary Research Assemblage Loop (SPIRAL) to examine children’s interactions in Auckland and Venice. While pristine playgrounds in cities like Auckland ensure safety, they isolate children (3-12 years old) from dy-namic urban environments. In contrast, Venice’s integrated spaces foster spontaneous play. We propose design interventions that balance safety and exploration, contributing to regenerative urbanism and equitable public spaces. The study concludes with open-ended questions to inspire future research.
Keywords: 3301 Architecture; 3304 Urban and regional planning; 4206 Public health